1988
DOI: 10.1021/bi00410a039
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous expression of the bifunctional thymidylate synthase-dihydrofolate reductase from Leishmania major

Abstract: The bifunctional thymidylate synthase-dihydrofolate reductase (TS-DHFR) of Leishmania major has been cloned and expressed in Escherichia coli and Saccharomyces cerevisiae. The strategy involved placing the entire 1560-bp coding sequence into a parent cloning plasmid that was designed to permit introduction of unique restriction sites at the 5'- and 3'-ends. In this manner, the entire coding sequence could be easily subcloned into a variety of expression vectors. High levels of TS-DHFR gene expression were driv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…Enzyme-The clone of the wild-type bifunctional TS-DHFR enzyme from L. major was a generous gift from C.-C. Kan and D. Matthews, then at Agouron Pharmaceuticals. This clone, harboring the pO2CLSA-4 plasmid in an E. coli Rue 10 expression vector, was used to obtain protein of high purity (Ͼ99%) using methods described previously for purification (28). The wild-type protein has both TS and DHFR activities similar to those reported previously (11,28,29).…”
Section: Methodsmentioning
confidence: 82%
See 1 more Smart Citation
“…Enzyme-The clone of the wild-type bifunctional TS-DHFR enzyme from L. major was a generous gift from C.-C. Kan and D. Matthews, then at Agouron Pharmaceuticals. This clone, harboring the pO2CLSA-4 plasmid in an E. coli Rue 10 expression vector, was used to obtain protein of high purity (Ͼ99%) using methods described previously for purification (28). The wild-type protein has both TS and DHFR activities similar to those reported previously (11,28,29).…”
Section: Methodsmentioning
confidence: 82%
“…This clone, harboring the pO2CLSA-4 plasmid in an E. coli Rue 10 expression vector, was used to obtain protein of high purity (Ͼ99%) using methods described previously for purification (28). The wild-type protein has both TS and DHFR activities similar to those reported previously (11,28,29). Mutations were made using a QuikChange mutagenesis kit (Stratagene).…”
Section: Methodsmentioning
confidence: 99%
“…They found that the recombinant protein accumulated to very high levels within E. coli, particularly under control of the T7 promoter, but most of the recombinant protein was present as inactive inclusion bodies and usually <2% of the soluble protein was catalytically active TS-DHFR. In contrast, Grumont et al (41) achieved better success in expressing the leishmanial TS-DHFR in yeast cells.…”
Section: Discussionmentioning
confidence: 96%
“…In general, however, the best way to identify the most effective expression system for a specific protein is largely empiric. For example, Grumont et al (41) expressed the bifunctional protein thymidylate synthetase-dihydrofolate reductase (TS-DHFR) of a protozoan parasite, Leishmania major, using several different vectors including those driven by tac, PL, and T7 RNA polymerase promoters. They found that the recombinant protein accumulated to very high levels within E. coli, particularly under control of the T7 promoter, but most of the recombinant protein was present as inactive inclusion bodies and usually <2% of the soluble protein was catalytically active TS-DHFR.…”
Section: Discussionmentioning
confidence: 99%
“…Roos. These clones were used to obtain protein of high purity by previously described methods for purification (7,17 (18).…”
mentioning
confidence: 99%